Africa, China, and the Meaning of Digital Data - Sorgner, Stefan Lorenz (Revista Ethika+, 2022)
Silicon-based transhumanists talk a lot about the implications of digitalization, whereby topics like mind-uploading, a digital consciousness, as well as the simulation argument are discussed most often. From a pragmatic perspective none of these issues is of any relevance. It seems to me that the following question is the most central one: How can we collect and use digital data in a democratic manner, as digital data are the new oil? For quite some time, we have seen global fights for digital data. China seems to have the most promising strategies for gathering digital data. Given the enormous interest of China in selected African countries, it needs to be analysed whether this development is in the long-term interest of these countries. In contrast to other analyses who primarily stress the neo-colonial aspects of this development, this article reveals some reasons why this cooperation also could be in the interest of the countries mentioned.